Adsorptive seawater desalination using MOF-incorporated Cu-alginate/PVA beads: Ion removal efficiency and durability. (April 2021) - Lee, Sang Joon; Lim, Hyeong Woo; Park, Sung Ho
Abstract: With the worsening water scarcity problem, seawater desalination has been receiving gradually increasing attention. Ion adsorptive desalination was introduced as one of the seawater desalination techniques. In our previous study, metal–organic framework (MOF)-incorporated single-network alginate (MOF-Alg(Cu)) beads were used to adsorb ions in seawater. In the present study, MOF-incorporated Cu-based alginate/PVA hydrogel (MOF-Alg(Cu)/PVA) beads were fabricated to enhance the ion adsorption desalination technique. Cu-based MOFs were successfully synthesized in situ on an interpenetrating polymer network (IPN). Given that the IPN hydrogel beads have high stability, the amount of MOF particles extracted during the adsorption of ions is reduced. The fabricated MOF-Alg(Cu)/PVA beads exhibit efficient removal of dissolved ions in artificial seawater and NaCl solution with varied concentrations. The ion adsorption characteristics were evaluated on the basis of adsorption kinetics, adsorption isotherms, and dosage of adsorbent. The repeat cycle tests show that more than half of the ion removal efficiency was maintained after 10 cycle tests. The concentration of artificial seawater was reduced to 1500 ppm by employing MOF-Alg(Cu)/PVA beads through a multistage experiment. Compared with other seawater desalination techniques, the proposed adsorptive desalination technique using MOF-Alg(Cu)/PVA beads will pave the way for developing a new ecofriendly and energy-saving approach. Graphical abstract: Image 1 Highlights: The effect of MOF-Alg(Cu)/PVA beads on seawater desalination was investigated. Cu-based MOFs were well synthesized in situ on an interpenetrating polymer network. The fabricated beads can be applied to a wide range of solution concentrations. The enhanced stability and reusability of the MOF-Alg(Cu)/PVA beads are verified. The concentration of seawater was reduced to 1500 ppm through a multistage test.